Report of E. Teumin about situation in 1944 - Starkauskas, Juozas (Genocidas ir rezistencija, 2004)
The report by E. Teumin, who was deputy head of the Soviet Information Bureau from 1940 to 1949, shows the efforts of part of the Soviet and party elite to subdue and enslave Lithuania by means other than terror. Unfortunately, the fact of the occupation was too obvious, and Lithuania chose the long, painful path of partisan warfare, which made propaganda measures ineffective.